Perbandingan kadar serum kreatinin pada pasien DM tipe 2 dengan frekuensi senam prolanis 1 kali per minggu dan 3 kali per minggu - Pangemanan, Angela; Marunduh, Sylvia R.; Engka, Joice N.A. (Universitas Sam Ratulangi, 2016)
Abstract: Creatinine is formed in muscles from creatinine phosphate and a byproduct of muscle metabolism. Creatinine is almost completely cleared from the body by filtration in the glomeruli. Physical activity can affect renal hemodynamics and protein excretion as well as creatinine level. Prolanis gymnastics is programmed for people who suffer from chronic diseases. This study was aimed to find out whether physical activity could affect serum creatinine by comparing Prolanis gymnastics practised 1 time/week and 3 times/week among patients with type 2 diabetes mellitus (T2DM). This was an experimental study with a pre-post test control group design. Subjects were 30 T2DM patients who practised Prolanis gymnastics at Husada Clinic Sario Manado, divided into two equal groups (15 people in each group). The results showed that in 1 time/week group, there was decreased creatinine level in 1 person (7%), increased creatinine level in 2 people (13%), and unchanged level in 13 people (87%). Meanwhile, in 3 times/week group there was no decrease of creatinine level but increased creatinine level in 4 people (27%) and unchanged in 11 people (73%). The Wilcoxon Signed Rank test showed a significant difference in creatinine levels between the two groups (p=0.001). Conclusion: Prolanis gymnastics 3 times/week was more effective than 1 time/week in affecting creatinine level in T2DM patients. Keywords: Prolanis gymnastics, creatinine, T2DM patientsÂ Abstrak: Kreatinin dibentuk di jaringan otot dari kreatinin fosfat dan merupakan produk sampingan metabolisme otot. Hampir seluruh kreatinin dikeluarkan dari tubuh melalui filtrasi glomerulus. Aktivitas fisik dapat memengaruhi hemodinamik ginjal dan ekskresi protein, termasuk kreatinin. Senam Prolanis merupakan program yang dibuat untuk masyarakat yang menderita penyakit kronis. Penelitian ini bertujuan untuk mengetahui pengaruh aktivitas fisik terhadap kadar kreatinin serum dengan membandingkan senam 1 kali/minggu dan 3 kali/minggu pada pasien diabetes melitus tipe 2 (DMT2). Jenis penelitian ialah eksperimental dengan pre-post control group test design. Data yang diperoleh diolah dengan menggunakan uji Wilcoxon Signed Ranks. Hasil penelitian mendapatkan subjek penyandang DMT2 berjumlah 30 orang (15 orang untuk masing-masing kelompok) yang mengikuti senam Prolanis di Klinik Husada Sario Manado. Pada kelompok 1 kali/minggu, terjadi penurunan kreatinin pada 1 orang (7%), kenaikan pada 2 orang (13%) dan tetap pada 13 orang (87%), sedangkan pada kelompok 3 kali/minggu, tidak terjadi penurunan kreatinin, tetapi ada kenaikan pada 4 orang (27%) dan tetap pada 11 orang (73%). Hasil uji Wilcoxon Signed Ranks mendapatkan perbedaan kadar kreatinin yang bermakna antara kedua kelompok (p=0,001). Simpulan: Senam Prolanis 3 kali/minggu lebih efektif daripada senam Prolanis 1 kali/minggu dalam memengaruhi kadar kreatinin pada pasien DMT2.Kata kunci: senam Prolanis, kreatinin, DMT2